E .mail Writing as a cross-cultural learning experience - Hocine, Nacira (Journal of Human Sciences, 2005)
This study looks into the cultural dimension involved in the e-mail correspondence between EFL students inAlgeriaand English students inBritain. E .mail entries were analysed to yield insights into the cross- cultural communication process. The data analysis focussed on the types of cultural information transmitted and effects of cultural assumptions and values on communication effectiveness. The findings revealed fundamental characteristics of both.Algerian and British cultures by the two groups of participants. It was also found that curiosity toward the other culture was a motivating factor for on-going correspondence but cultural presumptions were sometimes a hindrance for communication. Moreover, positive interpretations of cultural differences and empathy were key factors contributing to the removal of communication obstacles.Cross-cultural e. mail correspondence sensitized the participants to cultural differences and served as a learning experience for cross-cultural understanding